Aliterella atlantica gen. nov., sp. nov., and Aliterella antarctica sp. nov., novel members of coccoid Cyanobacteria - Rigonato, Janaina; Gama, Watson Arantes; Alvarenga, Danillo Oliveira; Branco, Luis Henrique Zanini [UNESP]; Brandini, Frederico Pereira; Genuário, Diego Bonaldo; Fiore, Marli Fatima (Microbiology Society, 2016)
Two Cyanobacteria isolated from South Atlantic Ocean continental shelf deep water and from a marine green algae inhabiting the Admiralty Bay, King George Island, Antarctica were investigated based on morphological and ultrastructural traits, phylogeny of 16S rRNA gene sequences, secondary structure of the 16S-23S internal transcribed spacer regions and phylogenomic analyses. The majority of these evaluations demonstrated that both strains differ from the genera of cyanobacteria with validly published names and, therefore, supported the description of the novel genus as Aliterella gen. nov. The identity and phylogeny of 16S rRNA gene sequences, together with the secondary structure of D1D1’ and BoxB intergenic regions, further supported the two strains representing distinct species: Aliterella atlantica gen. nov., sp. nov. (type SP469036, strain CENA595T) and Aliterella antarctica sp. nov. (type SP469035, strain CENA408T). The phylogenomic analysis of A. atlantica sp. nov. CENA595 T, based on 21 protein sequences, revealed that this genus belongs to the cyanobacterial order Chroococcidiopsidales. The isolation and cultivation of two geographically distant unicellular members of a novel cyanobacterial genus and the sequenced genome of the type strain bring new insights into the current classification of the coccoid group, and into the reconstruction of their evolutionary history.
Keywords: 16S-23S ITS; Antarctic; Brazilian atlantic Ocean; Phylogenome; Phylogeny; Ultrastructure